Effect of Storage Conditions on Germinability of Seeds of some Alpine Medicinal Plant Species - VINAY PRAKASH; HEMLATA BISHT; B. P. NAUTIYAL; R. S. CHAUHAN; HARISH PUROHIT; RAJIV VASHISTHA; M. C. NAUTIYAL; A. R. NAUTIYAL (Seed Research, 2026)
Seeds of some important high altitude medicinal plant species viz. Rheum emodi, Aconitum violaceum, Nardostachys jatamansi, Polygonum rumicifolium and Polygonum amplexicaule were stored in different storage conditions i.e. in polybag at 25°C, desiccator at 25°C and frige at 4-6°C. Germination percentage of all the species decreased with the increasing storage period. Seeds of all the species stored in polybags at 25°C showed rapid loss of viability with increasing storage period, the seeds stored in desiccator at 25°C, and refrigerator at 4-6°C showed viability for long period. Seeds of Rheum emodi, Aconitum violaceum, Nardostachys jatamansi, Polygonum rumicifolium and Polygonum amplexicaule stored in frige and desiccator lost 50% viability after 6, 4, 12, 4 and 6 months of storage respectively. In comparison to initial germination, 50% germinability of seeds was observed after 12, 6, 6 and 8 months of storage in seeds of Rheum emodi, Aconitum violaceum, Polygonum rumicifolium and Polygonum amplexicaule respectively at 4-6°C. Moisture content in stored seeds varies with storage condition as it increased in the seeds stored in polythene bag in comparison to the seeds stored in desiccator and frige.